Estimation of bonding nature using diamagnetic susceptibility1. Issue 41 (21st May 2015) - Tomiyasu, Keisuke; Sato, Toyoto; Orimo, Shin-ichi
<x xml:space="preserve">Abstract</x> A relationship between diamagnetic susceptibility and electronegativity was discovered, which provides a laboratory-based estimation method of bonding nature.